Optimization of Load Rejection Regulation for Compressed Air Energy Storage - Yinghao Wu; Xiankui Wen; Shihai Zhang; Qiang Fan; Huayang Ye; Chao Wu (Energies)
Given the shortcomings of compressed air energy storage systems in emergency response in power auxiliary research, especially in the scenario of decoupling from the power grid, an in-depth analysis is conducted. A set of energy release stage models with 10 MW compressed air energy storage equipped with an anti-overspeed system are set up. This research mainly focuses on the speed control of the two stages of the decoupled compressed air energy storage system: the soaring speed and the system recovery standby. By analyzing the influence of different cut-off valve actions on the decoupled speed, it is concluded that the key factor of speed control is the isolated expander. After the speed is controlled, the main factors affecting the speed control in the system are analyzed. As long as the expander is cut off, the high-temperature and high-pressure air will remain in the internal pipe and the heat exchanger of the system, which will cause the speed of the generator to soar again. A new load rejection control strategy is proposed based on the above analysis, in which the speed is smoothly reduced to 3000 r/min by the cut-off valve at the front end of the expander, and the residual working fluid is discharged. The results show that the optimized load rejection strategy reduces the speed increment by 89% compared to the traditional strategy, and reduces the recovery standby practice by 65%. Under 75% load conditions, the optimized load rejection strategy reduces the speed increment by 87% and the recovery standby practice by 41% compared to the traditional strategy. At 50% load conditions, the optimized load rejection strategy reduces the speed increment and standby time by 86% and 33%, respectively, compared to the traditional strategy. The key speed control index of the optimized load rejection strategy is much better than the traditional strategy, which significantly improves the control effect of accident emergencies.